EXPLORING MASLOW’S HIERARCHY OF HUMAN NEEDS IN “POLLYANNA” NOVEL - Fanny Virginia; Robby Satria (eScience Humanity Journal, 2022)
This descriptive qualitative research psychologically explored the hierarchy of human needs in “Pollyanna” novel. The quotations from all characters were examined seeing that the hierarchy of human needs is not only unfulfilled by the main character. However, other characters of the novel also have struggles in fulfilling the hierarchy of human needs. In collecting the data, the researchers applied library research because this research also used books and articles of the relevant object. Furthermore, the researchers analyzed the data by taking the descriptive analysis method. The data were analyzed by implementing Abraham H. Maslow’s theory regarding the hierarchy of human needs. The research result reported that the physiological needs, love and belonging needs, and self actualization are fulfilled by the characters of “Pollyanna” novel. As for the unfulfilled needs, those are safety needs and self-esteem needs as the needs that are not fulfilled by the characters. The safety needs are unfulfilled because the main character named Pollyanna did not get a proper room in Ms. Polly’s house. Also, Ms. Polly's self-esteem needs are unfulfilled because she does not feel respected because of the duty that assigns the woman to look after Pollyanna.